Phytopharmacological Review on The Ingredients of mudakku Chooranam: A Polyherbal Medicinal Powder - Divarjitha, T.; Mithursan, T.; Miraaj, R. (Faculty of Indigenous Medicine University of Colombo Sri Lanka, 2025)
Mudakku chooranam is a polyherbal medicinal power which is used in the treatment of variety of Vaadha diseases including arthritis, pain peptic ulcer It prepared with 21 herbal ingredients. This literary review study focused to develop scientific documentary evidences for the medicinal ingredients of mudakku chooranam. Date for this study were collected from related traditional books and research publications on website, collection data were processed and analyzed by using MS Excel. According to the results, all ingredients of Mudakku chooranam are herbal which are from fifteen different families. Out of 21 ingredients, 33% have pungent taste; 67% have hot potency and pungent efficacy, Based on the phytochemical analysis among the ingredients, 81% of ingredients have flavonoids; 71% have tannins and alkaloids, All of the ingredients have antioxidant activity; 90% of ingredients have antimicrobial and anti-inflammatory activities, Pungent taste and Hot Potency give heating effect (thee) in body which helps to balance the coldness or cooling effect of increased Vaadha dhosham according to Siddha pathophysiology. Flavonoids and phenolics act by regulating inflammatory mediators and help to reduce inflammation. Anti-inflammatory activity helps to reduce chronic inflammation and antioxidant activity helps to balance the oxidative damage. Therefore, this polyherbal preparation can be used to treat majority of Vaadha diseases, infectious diseases and other chronic inflammatory diseases. This review provides useful documentary evidence for the medicinal ingredients used to prepare Mudakku chooranam. However, further scientific studies related to elemental analysis, quantitative and qualitative analysis of phytochemicals and toxic substances should be performed in future.
Keywords: Mudakku chooranam; Phytopharmacological; Polyherbal ingredients